Formulasi Sabun Padat dari Biji Kopi Arabika (Coffea arabica L.) Kerinci - Dwi Mulyani (Jurusan Farmasi, Poltekkes Kemenkes Palembang, 2023)
Background: Kerinci coffee that is grown in the traditional way and gets a coffee stamp that applies a sustainable process. The caffeine content in coffee is an antioxidant that can prevent premature aging of the skin, is able to remove dead skin cells, smooth the skin, provide nutrition to the skin, eliminate body odor, remove acne scars and provide protection against ultraviolet rays. This study aims to obtain a good solid soap formula from Kerinci Arabica Coffee. Methods: Solid soap is made by the cold process method using a mixture of fatty oils and sodium hydroxide as the basic ingredients. The fatty oil used is a mixture of olive oil and coconut oil (Formula I/FI) and a mixture of olive oil and VCO (Formula II/FII). Results: Both formulas show good results in the form of solid, coffee-scented, milk chocolate color (FI) dark milk chocolate FII, FI soap has hard texture and FII has soft. The results of the test for water content FI = 11.3% and FII = 10.45%, the conditions according to SNI are less than 15%. The pH of FI soap is 9 and FII is 10, the pH test for 4 weeks shows a stable curve. Conclusion: Kerinci arabica coffee can be formulated into solid soap and meets the requirements for water content and pH